(untitled) (diségno, 2024)
On September 16, the 2024 edition of the Digital & Documentation conference took place. Now in its 7th edition, the event brings together professors, researchers, and scholars in the field of Representation to discuss the topic related to documentation practices: in this scenario, particular attention is given to digital technologies applied to historical buildings. [read more]